2020
DOI: 10.22159/ijpps.2020v12i9.38813
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Silver Nanoparticles Against Diethyl Nitrosamin and Carbon Tettrachloride-Induced Hepatocellular Carcinoma in Rats

Abstract: Objective: Hepatic cancer is known as primary liver cancer and hepatocellular carcinoma (HCC). Newly silver nanoparticles gained importance due to its advantages and multiple potential such as molecular imaging agent, antimicrobial, wound healing, anti-inflammatory and anticancer activity. The current study deals to assess therapeutic property silver nanoparticles (AgNPs) against diethylnitrosamine (DENA), and carbon tetrachloride (CCL4) induced hepatic cancer. Methods: Thirty male albino rats (200-250g)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…At the completion of the experiment, blood was taken out from the orbital sinus of fasting rats with a glass capillary according to Hassan et al [ 55 ]. To obtain serum, the collected whole blood was relocated into non-heparinized centrifuge tubes made of glass materials and allowed to clot at room temperature and then centrifuged at 3500× g for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…At the completion of the experiment, blood was taken out from the orbital sinus of fasting rats with a glass capillary according to Hassan et al [ 55 ]. To obtain serum, the collected whole blood was relocated into non-heparinized centrifuge tubes made of glass materials and allowed to clot at room temperature and then centrifuged at 3500× g for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…For preparation of basic ginger nanoparticles (GNB), 50 mg fine ginger powder with low solubility in water was mixed with 50 mg sodium bicarbonate buffer, then ground by mechanical ball mill using a planetary ball mill (Retsch PM 400, Germany) at (350 round/Sec) for 15 hrs. The color of ginger changed from yellow to yellowish white as a result of the ginger sodium salt formation [17].…”
Section: Preparation Of Ginger (G) Ginger Nanoparticles (Gnps) and Ginger Nano-base (Gnb)mentioning
confidence: 99%
“…Synthetic analogs and formulations of ginger have been developed, including combination with polymeric micelles [16] or nanoparticle-based encapsulation by poly-lactic-co-glycolic acids (PLGA) [14] or isolated ginger derived nanoparticles from ginger juice by using high power centrifugation [12], that exhibit greater chemical stability, systemic bioavailability and antioxidant, anti-inflammatory and antitumor activities than naturally occurring ginger. Therefore, we try to develop ginger nano-base particles by milling ginger with sodium bicarbonate [17], to increase ginger solubility and bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…One of these derivatives is curcumin, which is obtained from the plant Curcuma longa , frequently called turmeric. It has gained enormous importance for its exceptional antioxidant, anti-inflammatory, anti-carcinogenic, and anti-angiogenic activities with no noticeable toxicity [ 5 ]. Accumulated experimental evidence implies that curcumin interferes with a variety of molecular targets and processes involved in cancer [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diethylnitrosamine (DEN) is a potent genotoxic nitrosamine that is known to induce damage of the nuclear enzymes involved in DNA repair/replication and is typically used in experimental models to cause liver cancer. It has been demonstrated that DEN is metabolized into its active ethyl radical metabolite that interacts with DNA causing its mutation and chromosomal aberrations which would eventually lead to the development of hepatocarcinogenesis [ 5 ]. Additionally, the active metabolites of DEN generated by cytochrome isoform 2E1 (CYP 2E1) increase the oxidative stress level, leading to cytotoxicity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%